Use of the social media by the governor of Goiás: a marketing strategy or public communication? - Ribeiro, Eva Márcia Arantes Ostrosky; Mainieri, Tiago (Organicom, 2015)
This article reflects a graduate research the main objective of which is a study whether the social media could be a spacefor practice of public communication. For this we present the results of a case study of the Twitter of the governor of Goiás,Marconi Perillo. With this study one intends to highlight the discussion and debate of this theme that is considered to benodal and recent in the area of communication.